Evaluating the role of DNA evidence in sexual offence cases in Zambia between 2007 and 2014 - Makasa, Innocent (Division of Forensic Medicine and Toxicology, 2017)
Zambia has reported high incidences of sexual abuse against women and children in recent years. Zambian law categorises sexual offences into; rape, defilement, incest and others, with defilement constituting the majority of the cases (>89%). Between 2010 and 2012, only <39% of defilement cases were taken to court, and convictions were achieved in only 13% of the cases reported to the police. Literature was reviewed to determine factors which contributed towards the resolution of criminal cases, and it was found that DNA evidence was prominent in resolving crimes, specifically as an identification tool in sexual offences. Currently there is no empirical evidence describing how DNA evidence has been used in resolving sexual crimes in Zambia. The causes of low prosecution and conviction rates have also not been investigated. A retrospective study was therefore conducted to evaluate the role of DNA evidence in sexual offence cases in Zambia, reported to eight major police stations in Lusaka between 2007 to 2014 (n=1154). Sexual offence cases comprised rape (n=74, 6.4%), defilement of a child under the age of sixteen years (n=1028; 89.1%), incest (n=7; 0.6%) and others (n=45; 3.9%). Only 14 (0.1%) of the cases had forensic samples collected in the form of a vaginal swab for the sole purpose of determining the presence of semen. In all cases where a suspect was identified (60%), identification was based on the witness/victim testimonies, and in no case was forensic DNA evidence used to assist in identification or corroborate the testimonies. Overall, 28.1% cases were taken to court and the conviction rate was 12.4%. If no injuries were observed on a victim aged between 0 - 5 years, the case was not taken to court. It was also observed that the younger the victim, the more likely the accused was not identified (p < 0.001), victims did not know the date of occurrence (p < 0.001), and the case was closed due to insufficient evidence. These findings support the use of employing forensic DNA evidence in sexual offence cases to aid the identification of suspects, either in the absence of witness/victim testimonies or alongside as corroborative evidence, which is hypothesised to increase the number of cases prosecuted in Zambia. At the time of this study there was no standardised protocol for the forensic investigations of sexual offences in Zambia, which to some extent, led to numerous missing data. Development and use of the national protocol and use of a validated sexual assault evidence collection kit may help mitigate the deficiencies and inconsistencies witnessed during this study.